The Great Hack as a Form of Resistance Against the Use of Personal Data for Business Interests - Suada, Faiza Humaira; Maryani, Eni; Mahameruaji, Jimi Narotama (COMMENTATE: Journal of Communication Management, 2023)
This research is based on the documentary film “The Great Hack” which provides a detailed account of how Facebook and Cambridge Analytica harvested and utilized personal data for political agendas. The Great Hack aims to uncover the Cambridge Analytica case concerning the unethical use of personal data without user consent for business purposes. The research employs a case study methodology, incorporating interviews, observations, and a literature review. The findings reveal that The Great Hack depicts the unethical use of personal data, with Cambridge Analytica proven to have utilized Facebook users’ data without their consent. This data was employed to create psychographic models that predict an individual’s social and political behavior. Consequently, it can be concluded that there was an unethical use of personal data by Cambridge Analytica for business interests.